Analisis Kualitas Pelayanan Penerbitan Surat Keterangan Tempat Tinggal Orang Asing (SKTT-OA) pada Dinas Kependudukan dan Pencatatan Sipil Kota Surabaya - Moh. Afif Subhan; Ika Devy Pramudiana; M. Khairul Anwar; Dendy Patrija W (NAAFI: JURNAL ILMIAH MAHASISWA, 2024)
This study aims to analyze the quality of service in issuing the Certificate of Temporary Stay for Foreigners (SKTT-OA) at the Department of Population and Civil Registration (Dispendukcapil) in Surabaya City. Using a descriptive qualitative approach, this research refers to the service quality dimensions proposed by Parasuraman, Zeithaml, and Berry, which include tangible, reliability, responsiveness, assurance, and empathy. Data were collected through observation, interviews with staff and SKTT-OA applicants, as well as documentation related to the service process. The research findings indicate that, in general, the quality of service at Dispendukcapil Surabaya is adequate. The tangible dimension reflects complete facilities, although maintenance of some infrastructure such as computers and printers needs improvement. The reliability dimension shows high dependability with professionalism and good communication skills from the staff, including with Foreign Nationals (WNA). In the responsiveness dimension, the staff’s promptness in providing fast and responsive service to applicants’ needs is evident. However, in the assurance dimension, although data security guarantees and clear procedures are in place, inter-agency processes often cause delays. The empathy dimension is highly appreciated due to the friendly and attentive attitude of the Dispendukcapil staff toward WNA. This study concludes that the SKTT-OA service meets most of the quality standards but requires improvement in facility maintenance and inter-agency coordination. The recommendations include improving infrastructure maintenance, strengthening the online service system, providing continuous staff training, and conducting regular evaluations of applicant satisfaction to ensure service quality is maintained.